Sisi Gelap Pelaksanaan Penangkapan oleh Penyidik (Pertanggungjawaban Pidana Terhadap Pelaksanaan Tugas Jabatan) - Muchtar, Henni (Jurnal Demokrasi, 2011)
The law should be fair and struggle for the justice. Yet, the error catching is dark side for the application of law by apparatus especially for policeman. Because of that, improving and increasing the system of law is really crucial for our country especially for the criminal policy. The improvisation that should be done is in structure and substance from law criminal itself.Kata Kunci: Penangkapan, penahanan, penyidik pertanggung-jawaban, tugas jabatan